Improving MSME Performance through Innovation and Superior Service Quality - Bado, Basri; Dunakhir, Samirah (Inovasi Analisis Data, 2024)
This study investigates the impact of innovation and service quality on the performance of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Polewali Mandar Regency. Using a sample of 97 respondents from a population of 3,222 MSMEs, data were collected through a Likert scale questionnaire. Results indicate that both innovation and service quality significantly contribute to MSME success, enabling businesses to adapt to market changes and meet customer expectations. Moreover, innovation acts as a mediator, enhancing the influence of service quality on MSME performance. These findings underscore the importance of investing in service quality and fostering an environment conducive to innovation to promote the competitiveness and sustainability of MSMEs in Polewali Mandar Regency. This study offers valuable insights for stakeholders and policymakers seeking to support MSME development in the region, emphasizing the pivotal role of innovation and superior service quality in driving business success.